BIMBINGAN DAN PELATIHAN REMAJA DALAM MENGGUNAKAN JILBAB SESUAI SYARI’AT DI PERUMAHAN FARGESIA -BANTARGEBANG - Gian Prihastiwi; Rabiyannur Lubis; Akmal Rizki Gunawan Hasibuan (Universitas Islam 45 Bekasi, 2022)
Guidance and training activities for youth in using the headscarf according to the Shari'a in Fargesia housing are in the background because some of the teenagers there are still many who use the hijab but do not cover their aura. such as: the chest that is still visible or visible because the hijab is not allowed to unravel. Therefore, in this activity, the author provides guidance and training in using the hijab that is good and correct to the teenagers in the housing, as a reminder about the requirements for a good and correct hijab according to the Al-Quran. at the same time To be able to increase their knowledge about how to use or wear the hijab following Islamic Shari'a and to make this learning goal a success even in a Pandemic. Starting from the provision of material regarding the understanding of veiling, demands, and arguments about covering the genitals as well veiling by the Shari'a, and the conditions for the veil following the Shari'ah. The methods used in this activity are Community Education and Training. The purpose of this activity is so that teenagers can understand the ethics of using the hijab that is good and right and be able to get used to it in everyday life.